Impact of COVID-19 In-hospital Mortality in Chagas Disease Patients - Sperandio da Silva, Gilberto Marcelo; Mediano, Mauro Felippe Felix; Murgel, Michele Ferreira; Andrade, Patricia Mello; de Holanda, Marcelo Teixeira; da Costa, Andréa Rodrigues; Veloso, Henrique Horta; Carneiro, Fernanda Martins; Valete Rosalino, Cláudia Maria; de Sousa, Andréa Silvestre; Mendes, Fernanda de Souza Nogueira Sardinha; Pinheiro, Roberta Olmo; et al. (Frontiers in Medicine, 2022)
The COVID-19 virus infection caused by the new SARS-CoV-2 was first identified in Rio de Janeiro (RJ), Brazil, in March 2020. Until the end of 2021, 504,399 COVID-19 cases were confirmed in RJ, and the total death toll reached 68,347. The Evandro Chagas National Institute of Infectious Diseases from Oswaldo Cruz Foundation (INI-Fiocruz) is a referral center for treatment and research of several infectious diseases, including COVID-19 and Chagas disease (CD). The present study aimed to evaluate the impact of COVID-19 on in-hospital mortality of patients with CD during the COVID-19 pandemic period. This observational, retrospective, longitudinal study evaluated all patients with CD hospitalized at INI-Fiocruz from May 1, 2020, to November 30, 2021. One hundred ten hospitalizations from 81 patients with CD (58% women; 68 ±11 years) were evaluated. Death was the study's main outcome, which occurred in 20 cases. The mixed-effects logistic regression was performed with the following variables to test whether patients admitted to the hospital with a COVID-19 diagnosis would be more likely to die than those admitted with other diagnoses: admission diagnosis, sex, age, COVID-19 vaccination status, CD clinical classification, and the number of comorbidities. Results from multiple logistic regression analysis showed a higher risk of in-hospital mortality in patients diagnosed with COVID-19 (OR 6.37; 95% CI 1.78-22.86) compared to other causes of admissions. In conclusion, COVID-19 infection had a significant impact on the mortality risk of INI-Fiocruz CD patients, accounting for one-third of deaths overall. COVID-19 presented the highest percentage of death significantly higher than those admitted due to other causes during the COVID-19 pandemic.